2014
DOI: 10.1111/jnc.12836
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sphingolipid abnormalities following cerebral microendothelial hypoxia

Abstract: Hypoxia has been previously shown to inhibit the dihydroceramide (DHC) desaturase, leading to the accumulation of DHC. In this study, we used metabolic labeling with [3H]-palmitate, HPLC/MS/MS analysis, and specific inhibitors to show numerous sphingolipid changes after oxygen deprivation in cerebral microendothelial cells. The increased DHC, particularly long-chain forms, was observed in both whole cells and detergent-resistant membranes. This was reversed by reoxygenation and blocked by the de novo sphingoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
4
33
0
Order By: Relevance
“…It has recently been shown by lipid analysis that restricting oxygen to the brain leads to inhibition of dihydroceramide desaturase and the accumulation of dihydroceramides, dihydrosphingomyelins and dihydroglycosylceramides [42,43]. DHC is also seen in Hemorrhagic stroke [37] and this evidence of hypoxic injury to brain and can be detected by both HPTLC and HPLC/MS/MS (Fig.13).…”
Section: Methods For Measuring Specific Brain Lipidsmentioning
confidence: 93%
See 1 more Smart Citation
“…It has recently been shown by lipid analysis that restricting oxygen to the brain leads to inhibition of dihydroceramide desaturase and the accumulation of dihydroceramides, dihydrosphingomyelins and dihydroglycosylceramides [42,43]. DHC is also seen in Hemorrhagic stroke [37] and this evidence of hypoxic injury to brain and can be detected by both HPTLC and HPLC/MS/MS (Fig.13).…”
Section: Methods For Measuring Specific Brain Lipidsmentioning
confidence: 93%
“…DHC is also seen in Hemorrhagic stroke [37] and this evidence of hypoxic injury to brain and can be detected by both HPTLC and HPLC/MS/MS (Fig.13). They have a separate metabolic pathway from the more bioactive ceramides and S1P (Fig 13]) [42,43] and in fact little is known of the biological function of dihydrosphingosines. A myco-toxin found in corn (Fumonisin B1) inhibits de novo synthesis of sphingolipids and leads to increases in dihydrosphingosine and deoxysphingolipids, which may be responsible for some of the brain-specific brain structural deficits observed in different animals.…”
Section: Methods For Measuring Specific Brain Lipidsmentioning
confidence: 99%
“…The cerebral capillaries provide an active interface between blood and the brain and thus, regulates the passage of molecules into and out of the brain, including lipids. Sphingolipid signaling in cerebral endothelial cells appear to be highly selective of protective versus dysfunctional states (van Doorn et al 2012;Testai et al 2014;Prager et al 2015). Furthermore, accumulation of ceramides has been shown to induce endothelial dysfunction in the periphery .…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that SAH is associated with profound changes in the metabolism of sphingolipids, which result mainly in the increased production of Cer and DHC and decreased S1P. Sphingolipids are a family of membrane‐associated lipids that participate in multiple cellular signaling pathways and have become increasingly associated with brain pathologies from cognition to ischemia and hypoxia (Herr et al, ; Takahashi et al, ; Mielke et al, ; Testai et al, ). We sought to test this in a rat model of SAH and to compare the results with findings in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the levels of both sphingolipids had a strong linear correlation, suggesting a relationship of dependence between the two variables. Sphinganines (or dihydrosphingolipids) were until recently thought to be metabolically inactive biosynthetic intermediaries, but recent studies have illustrated that DHC and other sphinganines accumulate in hypoxic conditions and may regulate cell survival, cerebral microendothelial cell barrier function, and autophagy (Stiban et al, ; Breen et al, ; Siddique et al, ; Testai et al, ). Desaturases efficiently convert DHC into Cer, but the addition of exogenous C 2 ‐ or C 6 ‐Cer to cell cultures does not modify the levels of DHC, indicating that the metabolism of DHC into Cer is irreversible (Qin et al, ).…”
Section: Discussionmentioning
confidence: 99%